1994
DOI: 10.1161/01.hyp.24.6.802
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol abolishes the hypotensive effect of clonidine in spontaneously hypertensive rats.

Abstract: This study tested the hypothesis that concurrent ethanol administration attenuates the hypotensive effect of clonidine. Four groups of spontaneously hypertensive rats matched for baseline systolic pressure and body weight were randomly assigned the following treatments: (1) water (control), (2) ethanol, (3) clonidine, and (4) ethanol plus clonidine for 13 weeks. Ethanol was provided in the drinking water as 5% for 1 week, 10% for the next 2 weeks, and 20% from week 4 to 13. Starting from similar baseline systo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 30 publications
0
16
1
Order By: Relevance
“…In effect, clonidine increased heart rate variability indices (SDRR and rMSSD) in rats receiving the higher concentration of ethanol. Second, the hypotensive response to intracisternally administered clonidine was attenuated in ethanol chronically fed SHRs whose baseline blood pressure was similar to that of control SHRs (Abdel-Rahman, 1994), suggesting that differences in baseline blood pressure in the present study may not account for the attenuated clonidine hypotension in ethanol-fed rats. Third, the antagonistic ethanol-clonidine hemodynamic interaction has been demonstrated in arterial barodenervated rats (El-Mas et al, 1994b; El-Mas and Abdel-Rahman, 1997) whose baseline blood pressure was less than that seen in ethanol-fed rats in the present study.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…In effect, clonidine increased heart rate variability indices (SDRR and rMSSD) in rats receiving the higher concentration of ethanol. Second, the hypotensive response to intracisternally administered clonidine was attenuated in ethanol chronically fed SHRs whose baseline blood pressure was similar to that of control SHRs (Abdel-Rahman, 1994), suggesting that differences in baseline blood pressure in the present study may not account for the attenuated clonidine hypotension in ethanol-fed rats. Third, the antagonistic ethanol-clonidine hemodynamic interaction has been demonstrated in arterial barodenervated rats (El-Mas et al, 1994b; El-Mas and Abdel-Rahman, 1997) whose baseline blood pressure was less than that seen in ethanol-fed rats in the present study.…”
Section: Discussionmentioning
confidence: 55%
“…This clinically important phenomenon has been demonstrated in experimental animals in our previous reports, which showed that ethanol, administered acutely or chronically, counteracts the hypotensive effect of clonidine and related antihypertensive agents (Abdel-Rahman et al, 1992;Abdel-Rahman, 1994;El-Mas et al, 1994b). In contrast, peripherally mediated hypotensive responses elicited by hydralazine, nitroprusside, or hexamethonium are not influenced by ethanol (AbdelRahman et al, 1992;El-Mas and Abdel-Rahman, 1999).…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…Cardiac output was measured by Cardiomax (Columbus Instruments, Columbus, OH) interfaced with a computer, based on the thermodilution technique with a thermocouple in the thoracic aorta via the carotid artery (2,19).…”
Section: Methodsmentioning
confidence: 99%
“…Abdel-Rahman 85 reported that the BP increase was not different between ethanol-fed (5-20% in drinking water) spontaneously hypertensive (SH) rats and control SH rats during a 13-week observation period. The depressor effect of clonidine, however, was reduced in the ethanol-fed SH rats, suggesting a change in the neural regulation of BP.…”
Section: Experimental Studiesmentioning
confidence: 99%